Liquid biopsies of solid tumors: non-small-cell lung and pancreatic cancer - Kalubowilage, Madumali (Kansas State University, 2017)
Cancer is a group of diseases that are characterized by uncontrolled growth and spread of cells. In order to treat cancer successfully, it is important to diagnose cancers in their early stages, because survival often depends on the stage of cancer detection. For that purpose, highly sensitive and selective methods must be developed, taking advantage of suitable biomarkers. The expression levels of proteases differ from one cancer type to the other, because different cancers arise from different cell types. According to the literature, there are significant differences between the protease expression levels of cancer patients and healthy people, because solid tumors rely on proteases for survival, angiogenesis and metastasis. Development of fluorescence-based nanobiosensors for the early detection of pancreatic cancer and non-small-cell lung cancer is discussed in this thesis. The nanobiosensors are capable of detecting protease/arginase activities in serum samples over a broad range. The functionality of the nanobiosensor is based on Förster resonance energy transfer and surface energy transfer mechanisms. The nanobiosensors for protease detection feature dopamine-coated Fe/Fe₃O₄ nanoparticles, consensus (cleavage) peptide sequences, meso-tetra(4-carboxyphenyl)porphine (TCPP), and cyanine 5.5. The consensus peptide sequences were synthesized by solid-supported peptide synthesis. In this thesis, improved consensus sequences were used, which permit faster synthesis and higher signal intensities. TCPP, which is the fluorophore of the nanoplatform, was connected to the N-terminal end of the oligopeptides while it was still on the resin. After the addition of TCPP, the TCPP-oligopeptide was cleaved off the resin and linked to the primary amine groups of Fe/Fe₃O₄-bound via a stable amide bond. In the presence of a particular protease, the consensus sequences attached to the nanoparticle can be cleaved and release TCPP to the aqueous medium. Upon releasing the dye, the emission intensity increases significantly and can be detected by fluorescence spectroscopy or, similarly, by using a fluorescence plate reader. In sensing of arginase, posttranslational modification of the peptide sequence will occur, transforming arginine to ornithine. This changes the conformational dynamics of the oligopeptide tether, leading to the increase of the TCPP signal. This is a highly selective technology, which has a very low limit of detection (LOD) of 1 x 10⁻¹⁶ molL⁻¹ for proteases and arginase. The potential of this nanobiosensor technology to detect early pancreatic and lung cancer was demonstrated by using serum samples, which were collected from patients who have been diagnosed with pancreatic cancer and non-small cell lung cancer at the South Eastern Nebraska Cancer Center (lung cancer) and the University of Kansas Cancer Center (pancreatic cancer). As controls, serum samples collected from healthy volunteers were analyzed. In pancreatic cancer detection, the protease/arginase signature for the detection of pancreatic adenocarcinomas in serum was identified. It comprises arginase, MMPs -1, - 3, and -9, cathepsins -B and -E, urokinase plasminogen activator, and neutrophil elastase. For lung cancer detection, the specificity and sensitivity of the nanobiosensors permit the accurate measurements of the activities of nine signature proteases in serum samples. Cathepsin -L and MMPs-1, -3, and -7 permit detecting non-small-cell lung-cancer at stage 1.
Keywords: liquid biopsy; pancreatic cancer; non small cell lung cancer; fluorescence detection; nanobiosensor; cancer detection